Impact of Concurrent Medication Use on Pancreatic Cancer Survival—SEER-Medicare Analysis. (August 2018) - Beg, Muhammad S.; Gupta, Arjun; Sher, David; Ali, Sadia; Khan, Saad; Gao, Ang; Stewart, Tyler; Ahn, Chul; Berry, Jarett; Mortensen, Eric M.
Abstract : Objectives: Preclinical studies have suggested that non-antineoplastic medication use may impact pancreatic cancer biology. We examined the association of several medication classes on pancreatic cancer survival in a large medical claims database. Materials and Methods: Histologically confirmed pancreatic adenocarcinoma diagnosed between 2006 and 2009 were analyzed from the Surveillance, Epidemiology, and End Results-Medicare database with available part D data. Drug use was defined as having 2 prescriptions filled within 12 months of pancreatic cancer diagnosis. The following medication classes/combinations were analyzed: β-blocker, statin, insulin, metformin, thiazolidinedione, warfarin, heparin, β-blocker/statin, metformin/statin, and β-blocker/metformin. Multivariable Cox proportional hazard models adjusting for age, sex, race, stage at diagnosis, site of cancer, and Charlson comorbidity index were constructed to test the association between medication classes and overall survival. Results: A total of 13, 702 patients were included in the study; median age 76 years, 42.5% males, 77.1% white. The most common anatomic site and stage at diagnosis were head of the pancreas (49.9%) and stage 4 (49.6%), respectively. Ninety-four percent of patients died in the follow-up period (median overall survival 5.3 mo). Multivariable Cox regression analysis showed that use of β-blockers, heparin, insulin, and warfarin were significantly associated with improved survival ( P <0.05 for each one), whereas metformin, thiazolidinedione, statin, and combination therapies were not. Conclusions: In this study, use of β-blockers, heparin, insulin, and warfarin were associated with improved survival in patients with pancreatic cancer. Additional studies are needed to validate these findings in the clinical setting.